Comparative Evaluation of Different Test Combinations for Diagnosis of Mycobacterium avium Subspecies paratuberculosis Infecting Dairy Herds in India - Garg, Rajni (Biomed Res Int, 2015)
A total of 355 cows were sampled (serum, n = 315; faeces, n = 355; milk, n = 209) from dairy farms located in the Punjab state of India. Faeces and serum/milk samples were screened by acid fast staining and “indigenous ELISA,” respectively. IS900 PCR was used to screen faeces and milk samples. Bio-load of MAP in dairy cows was 36.9, 15.6, 16.3, and 14.4%, using microscopy, serum ELISA, milk ELISA and milk PCR, respectively. Estimated kappa values between different test combinations: serum and milk ELISA, faecal microscopy and faecal PCR, milk ELISA and milk PCR, faecal PCR and serum ELISA were 0.325, 0.241, 0.682, and 0.677, respectively. Estimation of the relative sensitivity and specificity of different tests in the present study indicated that “serum ELISA” and “milk ELISA” were good screening tests, add “milk PCR” was “confirmatory test” for MAP infection. Combination of milk ELISA with milk PCR may be adopted as a model strategy for screening and diagnosis of JD in lactating/dairy cattle herds in Indian conditions.